The Effectiveness Of Education Using Vidio Is Determined Nutritional Knowledge In Mothers With Low Nutritional Children At At Sanur Health Center Nunukan District - Rida Veranata Simanungklit,; Retno Palupi Yonni Siwi, (Journal of Health Science Community, 2025)
Toddlers who lack sufficient nutritional intake will most likely have a decreased immune system, making them susceptible to infectious diseases which can affect their appetite and absorption of nutrients, causing malnutrition. Toddlers who often experience infectious diseases and malnutrition will easily experience growth and development disorders at this age, which will affect the child's level of health and intelligence as well as productivity in the subsequent growth period. This research aims to determine the effectiveness of education using videos on nutritional knowledge in mothers of malnourished toddlers. This research is a quantitative research with a pre-experimental research design, one group pre-test post test with a cross sectional approach. The sample in this study was 72 mothers who had malnourished toddlers in the working area of the Sanur Health Center, Nunukan Regency, using a purposive sampling technique. The Wilcoxon statistical test was used to determine the effectiveness of education using videos on nutritional knowledge in malnourished mothers of toddlers.The results of research from 72 respondents, almost all respondents experienced an increase in knowledge, namely 41 respondents (55,9%) who had a sufficient level of knowledge and 31 respondents (43,1%) who had a good level of knowledge. .The results of bivariate analysis using the Wilcoxon test obtained a p value of 0.000 < 0.05, so the HI was accepted because there was the effectiveness of education using videos on nutritional knowledge in malnourished mothers of toddlers.It can be used as evaluation material to improve educational methods that are more interesting and it is hoped that it can increase knowledge about nutrition in toddlers.